Comparison of Final Results Using Combination AHP-VIKOR And AHP-SAW Methods In Performance Assessment (Case Imanuel Lurang Congregation) - Devi Valentino Waas; I Gede Iwan Sudipa; I Putu Agus Eka Darma Udayana (IJISTECH (International Journal of Information System and Technology), 2022)
Determination of the final result in determining the decision is to determine the best alternative from several existing alternatives based on several predetermined criteria. The criteria are measures, rules, or standards for making decisions. It can be done by combining several Multi-Criteria Decision Making (MCDM) methods such as AHP, VIKOR, SAW, TOPSIS, and others to get the best decision results. The Analytical Hierarchy Process (AHP) method is one of the MCDM methods with advantages at the criteria weighting stage. It uses a consistency test to see whether the weights obtained are consistent. In comparison, the VIKOR and SAW methods are also of MCDM methods but do not apply the weighting consistency test. With the advantages and disadvantages of each MCDM method, it is possible to combine several existing methods to provide better solutions or alternatives. This study compares the ranking results between the combination of the AHP-VIKOR method and the combination of the AHP-SAW method in a performance appraisal case study. The AHP method is used to weight the criteria and sub-criteria, while the VIKOR and SAW methods are used in the alternative ranking process. The test results show differences in the alternative ranking results between the two combinations of MCDM methods used.